Long-term mineral transformation of Ca-rich oil shale ash waste - Leben, Kristjan; Mõtlep, Riho; Paaver, Peeter; Konist, Alar; Pihu, Tõnu; Paiste, Päärn; Heinmaa, Ivo; Nurk, Gunnar; Anthony, Edward J.; Kirsimäe, Kalle (Elsevier, 2018)
Power generation and other industries using solid fossil fuels like coal, lignite, oil shale and peat are responsible for producing large quantities of solid residues that are often chemically reactive and/or unstable and are disposed in holding ponds and deposition sites. Stability and long-term behaviour of such deposits are typically studied in short-term laboratory experiments that cannot describe nor predict long-term changes taking place in these materials. Here, we study long-term (>40 years) transformations, in highly alkaline conditions, of the Ca-rich ash deposit in Estonia composed of oil shale processing residues from the Eesti power plant. Detailed mineralogical, chemical and micromorphological analyses using X-ray diffraction, X-ray fluorescence, 29Si nuclear magnetic resonance, scanning electron microscopy and other methods were applied in order to identify the composition of the waste with a focus on formation and transformation of semicrystalline phases in the deposit. The results show progressive formation of calcium-silicate-hydrate (C-S-H) type phase at the expense of silicate minerals and amorphous glass phases with increasing depth and age of the sediments, from about 25% in the upper part of the depository to over 60% in the oldest-deepest part. This demonstrates that over time the high alkalinity of the ash is responsible for initiating natural alkali-activation. The formation of C-S-H-type phases increases the mechanical strength of the sediment and ensures long-term stability of waste deposits. These findings may encourage the use of these ashes in binder or other construction material production or as construction aggregates.
Keywords: C-S-H; Alkali-activation; Oil shale ash; Mineralogy; Stability; Ash utilisation